2012
DOI: 10.3945/jn.112.159939
|View full text |Cite
|
Sign up to set email alerts
|

Bitter Melon Seed Oil-Attenuated Body Fat Accumulation in Diet-Induced Obese Mice Is Associated with cAMP-Dependent Protein Kinase Activation and Cell Death in White Adipose Tissue

Abstract: The aim of this study was to investigate the antiadiposity effect of bitter melon seed oil (BMSO), which is rich in the cis-9, trans-11, trans-13 isomer of conjugated linolenic acid. In Expt. 1, C57BL/6J mice were fed a butter-based, high-fat diet [HB; 29% butter + 1% soybean oil (SBO)] for 10 wk to induce obesity. They then continued to receive that diet or were switched to an SBO-based, high-fat diet alone (HS; 30% SBO) or containing bitter melon seed oil (BMSO) (HBM; 15% SBO + 15% BMSO) for 5 wk. The body f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 42 publications
7
50
3
Order By: Relevance
“…Sathishsekar and Subramanian (2005) found that in vivo antioxidant efficacy of bitter melon extracts has highlighted the increased activity of naturally occurring hepatic antioxidant enzymes. Bitter melon possesses antioxidant, anti-tumour, anti-bacterial, anti-inflammatory, anti-viral, anti-obesity, anti-hypertension as well as antihyperglycaemic effects (Ahmad et al, 2012;Chen et al, 2012;Hsu, Fang, Liu, & Chen, 2013;. More recently, Chang et al (2015) found that the triterpenes 3β,25-dihydroxy-7β-methoxycucurbita-5,23(E)-diene and 3β,7β,25-trihydroxycucurbita-5,23(E)-dien-19-al isolated from bitter melon have insulin-sensitizing and insulin-substitution functions, which are correlated to their effects on inhibiting proteintyrosine phosphatase-1B (PTP-1B) and activating AMP-activated protein kinase (AMPK) inhibitor, respectively.…”
Section: Bitter Melonmentioning
confidence: 99%
“…Sathishsekar and Subramanian (2005) found that in vivo antioxidant efficacy of bitter melon extracts has highlighted the increased activity of naturally occurring hepatic antioxidant enzymes. Bitter melon possesses antioxidant, anti-tumour, anti-bacterial, anti-inflammatory, anti-viral, anti-obesity, anti-hypertension as well as antihyperglycaemic effects (Ahmad et al, 2012;Chen et al, 2012;Hsu, Fang, Liu, & Chen, 2013;. More recently, Chang et al (2015) found that the triterpenes 3β,25-dihydroxy-7β-methoxycucurbita-5,23(E)-diene and 3β,7β,25-trihydroxycucurbita-5,23(E)-dien-19-al isolated from bitter melon have insulin-sensitizing and insulin-substitution functions, which are correlated to their effects on inhibiting proteintyrosine phosphatase-1B (PTP-1B) and activating AMP-activated protein kinase (AMPK) inhibitor, respectively.…”
Section: Bitter Melonmentioning
confidence: 99%
“…Recently, we demonstrated that bitter melon seed oil (BMSO) is more potent than soybean oil, which has approximately the same amount of polyunsaturated fatty acid (PUFA), in attenuating high saturated fatty acid (SFA) diet-induced adiposity and hepatic steatosis in C57BL/6J mice [4,5]. BMSO is enriched in a fatty acid characterized by the presence of conjugated triene (i.e., cis -9, trans -11, trans -13 isomer of conjugated linolenic acid [6]), also termed α-eleostearic acid (α-ESA), which has potential as a functional lipid.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the anti-adiposity effect of BMSO is associated with cAMP-dependent protein kinase (PKA) activation and cell death in white adipose tissue (WAT) [4]. In mice subjected to a BMSO diet, their WAT had delipidative, inflammatory, browning, apoptosis, and autophagy characteristics (determined by histochemistry combined with proteomic approaches), indicating a dynamic repair/remodel process [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical trials have shown that plant extracts, including the São Caetano melon extract, have therapeutic potential against diabetes and metabolic dysfunction related to obesity in animals (Chen et al, 2012;Alam et al, 2015). The effects of this plant on mitochondrial function, during the accumulation of liver fat associated with obesity, were identified by .…”
Section: Obesity Reductionmentioning
confidence: 99%